A comprehensive CFD approach of a thermal analysis of a braking discs system under different design conditions - F. Orlandi; M. Coccetta; S. Meleti; M. Milani; L. Montorsi (International Journal of Thermofluids)
A braking system is a fundamental part of any vehicle and represents a very complex topic due to its highly coupled phenomena taking place at once during its functioning. Serving as an extension of a previous work from the same authors, this paper extends the approach applied to a single braking discs coupled to a complete braking system. With means of a wall relative velocity approach coupled with a thermal energy dissipation cycle the braking event is modelled in a multiphase air/oil system. Two different lubricating oil inlets, vertical and horizontal, were investigated on the cooling efficiency of the system. The investigation was carried over the same operating conditions defined by the main operating parameters, defining the braking cycle and the machine characteristics. The different configuration was found out to lead to a slight improving in efficiency for the horizontal configuration seemingly linked to the different oil accumulation into the discs’ chamber due to the different ability of the system within the cooling oil circulation.